A First Step in the Quest for the Active Constituents in Filipendula ulmaria (Meadowsweet): Comprehensive Phytochemical Identification by Liquid Chromatography Coupled to Quadrupole-Orbitrap Mass Spectrometry - Bijttebier, Sebastiaan; Van der Auwera, Anastasia; Voorspoels, Stefan; Noten, Bart; Hermans, Nina; Pieters, Luc; Apers, Sandra (Planta Medica, 2016)
Filipendula ulmaria (meadowsweet) is traditionally used for the treatment of inflammatory diseases and as a diuretic and antirheumatic. Extracts of Filipendulae herba are on the market in the European Union as food supplements. Nevertheless, its active constituents remain to be revealed. During this study, the phytochemical composition of Filipendulae Ulmariae Herba was comprehensively characterised for the first time with two complementary generic ultrahigh-performance liquid chromatography-photodiode array-accurate mass mass spectrometry methods. Selective ion fragmentation experiments with a hybrid quadrupole-orbital trap mass spectrometer significantly contributed to compound identification: a total of 119 compounds were tentatively identified, 69 new to F. ulmaria. A rich diversity of phenolic constituents was detected and only a few non-phenolic phytochemicals were observed. Metabolisation and pharmacological studies should be conducted to investigate which of these constituents or metabolites there of contribute to the activity of F. ulmaria after oral intake.
Keywords: Filipendula ulmaria; Rosaceae; meadowsweet; LC-PDA-amMS; flavonoids; salicylic acid derivatives; tannins